2011
DOI: 10.4088/jcp.10m06304
|View full text |Cite
|
Sign up to set email alerts
|

Gender, HIV Status, and Psychiatric Disorders

Abstract: Objective More than thirty years after the onset of the HIV epidemic, there is no information on the prevalence of psychiatric disorders among HIV-positive individuals in the general population. We sought to compare the prevalence of 12-month psychiatric disorders among HIV-positive and HIV-negative adults stratified by sex, and to examine the differential increase in risk of a psychiatric disorder as a function of the interaction of sex and HIV status. Methods Face-to-face interviews conducted between 2004 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 50 publications
(69 reference statements)
1
29
1
Order By: Relevance
“…The presence of hypertension/atherosclerosis, hepatic disease, cardiovascular disease, gastrointestinal disease, arthritis, venereal disease, or other medical condition was associated with a greater likelihood of having BPD, even after adjusting for demographic characteristics and psychopathology. The NESARC data also revealed that PDs were associated with self-reported HIV status (Lopes et al, 2012). Compared to their HIV-negative sex-matched counterparts, HIV-positive men were more likely to have a PD (43.17% vs. 23.28%; OR = 2.50).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of hypertension/atherosclerosis, hepatic disease, cardiovascular disease, gastrointestinal disease, arthritis, venereal disease, or other medical condition was associated with a greater likelihood of having BPD, even after adjusting for demographic characteristics and psychopathology. The NESARC data also revealed that PDs were associated with self-reported HIV status (Lopes et al, 2012). Compared to their HIV-negative sex-matched counterparts, HIV-positive men were more likely to have a PD (43.17% vs. 23.28%; OR = 2.50).…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between MDD and HIV is complex, as depression can be a risk factor for HIV acquisition as well as a consequence of HIV infection (Smit et al, 2006, Simoni et al, 2011). However, MDD has long been recognized as a predictor of negative clinical outcomes among people with HIV (Bing et al, 2001, Simoni et al, 2011, Owe-Larsson et al, 2009, Lopes et al, 2012). Persons with depression initiate anti-retroviral treatment (ART) at lower CD4 counts than people without mental illness, and depressed patients are much less likely to adhere to ART than patients who are not depressed (Tegger et al, 2008, Gonzalez et al, 2011, Nakimuli-Mpungu et al, 2012a, Kaharuza et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The development of these disorders has been proposed to be due to the psychosocial burden that is associated with the diagnosis of HIV positive status (Lichtenstein, Laska et al 2002), stress stemming from occupational-related problems, lack of social support, cultural biases associated with infection, and/or resource-poor environments (Brown 2001; Wohl, Galvan et al 2010; Kamau, Kuria et al 2012). It is estimated that 30 - 50% of people living with HIV have a stress-related mood disorder such as depression, compared to only 6.5% of the general population (Hinkin, Castellon et al 2002; Lopes, Olfson et al 2012). Psychological problems can arise at a very young age in patients chronically infected with HIV (Gadow, Angelidou et al 2012), with anxiety and depression being more common in females (Mellins, Elkington et al 2012).…”
Section: ) Introductionmentioning
confidence: 99%